2020
DOI: 10.1016/j.radcr.2020.10.006
|View full text |Cite
|
Sign up to set email alerts
|

A case report of fetus in fetu with an aorta-like structure visualized by contrast-enhanced CT

Abstract: Fetus in fetu (FIF) is a rare congenital anomaly resulting from abnormal embyogenesis in monochorionic diamniotic twins and appears as a cystic mass containing fetus-like structures mainly in the retroperitoneum of infants. Although there is a theory that FIF is a highly differentiated teratoma, it is commonly distinguished from teratoma as a mass containing a vertebral axis with appropriate arrangement of limbs or other organs around this axis. Here we present a case of FIF with aorta-like structure visualize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…According to the teratoma theory, FIF is a specialized form of teratoma with well-differentiated, highly organized, and mature organs. It shows organ differentiation, including the original heart, brain, eyeballs, intestines, and limbs, and thus, FIF is considered a highly differentiated teratoma ( 4 ). It has also been reported that teratomas and FIF appear at the same time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the teratoma theory, FIF is a specialized form of teratoma with well-differentiated, highly organized, and mature organs. It shows organ differentiation, including the original heart, brain, eyeballs, intestines, and limbs, and thus, FIF is considered a highly differentiated teratoma ( 4 ). It has also been reported that teratomas and FIF appear at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Normal twins are deformed as symmetrical conjoined twins. FIF might result from abnormal embryogenesis in a diamniotic monochorionic twin pregnancy ( 4 , 6 ). In the early stage of embryonic development (blastocyst stage) of the fertilized egg, the totipotent cell cluster in the blastocyst divides into two or more cell clusters.…”
Section: Introductionmentioning
confidence: 99%
“…However, fetus in fetu can be found in adults [4] and in pregnant women [5] , the oldest patient with fetus in fetu recorded in the literature was 47 years old at diagnosis [6] . Fetus in fetu can parasitize any part of the host's body; however, the abdominal cavity and retroperitoneum are the most common sites [2 , 7 , 8] followed by the sacrococcygeal region and the abdominal wall. Other rare sites, such as the back, mouth and upper jaw, have also been reported, and very few cases have occurred in the brain [9 , 10] , mouth [11 , 12] , neck [13] , chest [14] and scrotum [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Fetus in fetu (FIF) is a rare congenital anomaly with an incidence of one per 500 000 births [ 1 ]. Taher et al found 224 FIF reported cases [ 2 ].…”
Section: ⧉ Introductionmentioning
confidence: 99%